1995
DOI: 10.1111/j.1600-051x.1995.tb00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic criteria for the efficiency of non‐surgical periodontal therapy in advanced periodontitis

Abstract: The aim of the study was to find out which clinical, radiographic and microbiological variables can be used as prognostic criteria for the efficiency of the commonly used initial treatment protocol comprising scaling, root planing and instruction on oral hygiene in advanced adult periodontitis. 46 patients (mean age 48 years) with untreated, advanced periodontitis volunteered for the study. The clinical examination included recordings of plaque, gingival and calculus indices, probing pocket depths, bleeding an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 61 publications
2
21
0
3
Order By: Relevance
“…Studies using dark‐field and phase contrast microscopy reported significant reductions in the percentage of motile rods and spirochetes after scaling and root planing and a concomitant increase in the percentage of cocci and non‐motile microorganisms 33‐35 . Other investigations noted minimal effects of scaling and root planing on the subgingival microbiota, especially for species such as A. actinomycetemcomitans 36,37 . In the present study, at T2, the number of test and control teeth positive for A. actinomycetemcomitans showed a decrease, whereas positive samples for S. mutans showed an increase.…”
Section: Discussionsupporting
confidence: 47%
“…Studies using dark‐field and phase contrast microscopy reported significant reductions in the percentage of motile rods and spirochetes after scaling and root planing and a concomitant increase in the percentage of cocci and non‐motile microorganisms 33‐35 . Other investigations noted minimal effects of scaling and root planing on the subgingival microbiota, especially for species such as A. actinomycetemcomitans 36,37 . In the present study, at T2, the number of test and control teeth positive for A. actinomycetemcomitans showed a decrease, whereas positive samples for S. mutans showed an increase.…”
Section: Discussionsupporting
confidence: 47%
“…20,27,[33][34][35][36][37][38][39][40][41] Additionally, the present sampling method was adjusted to the restrictions due to the study population. 20,27,[33][34][35][36][37][38][39][40][41] Additionally, the present sampling method was adjusted to the restrictions due to the study population.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical examination was carried out by only one researcher (AMH) and smoking status of the participant was unknown to the examiner. The oral health indices recorded were visible plaque index (VPI), bleeding on probing (BOP), 30 root calculus (RC), probing depth (PD), and attachment loss (AL), which was considered normal at values <2 mm 31‐33 . VPI and RC were recorded from index teeth, and BOP and PD were measured from all teeth and at four sites.…”
Section: Methodsmentioning
confidence: 99%